Konsep MVC Pada Rancang Bangun Aplikasi Sistem Informasi Rekrutmen Karyawan Berbasis Web - Ishak Komarudin; Hariyanto; Rahdian Kusuma Atmaja (LPPM Universitas Bina Sarana Informatika, 2021)
Qualified employees are one of the important factors in improving company performance, therefore the employee recruitment system is an important thing to fix, so that companies get professional employees quickly and according to their needs. PT. Alief Anaradar Kulahu currently still uses conventional methods in the employee recruitment process, starting from filing documents, entrance examinations, interview tests, and so on. The HR Division also needs to prepare a special room to store files for prospective employees, so they are not lost or damaged. The increasing pile of files will also make it difficult for HR staff to find data on prospective employees to be processed. This research aims to design a web-based employee recruitment information system to assist the HR division in managing data on prospective employees of PT. Alief Anaradar Kulahu. The web-based application is designed using the PHP programming language and MySQL DBMS, by implementing the MVC (Model View Controller) concept in its programming techniques. The implementation of the MVC concept aims to make it easier for web developers to design applications, because it separates the data (Model) from its appearance (View) and how to process it (Controller). The result of this research is an application that changes the way HR division staff work from manual to computerized, making it faster, more effective and efficient. The research also provides clear instructions on how to properly design web-based information systems, so that in the future it will make it easier for web developers when they have to repair or develop systems. Keywords: MVC Concept, Web Application, Employee Recruitment Information System.